Survival after pelvic exenteration for T4 rectal cancer. Issue 1 (1st December 2014) - Kusters, M; Austin, K K S; Solomon, M J; Lee, P J; Nieuwenhuijzen, G A P; Rutten, H J T
Abstract: Background: The purpose of this study was to analyse retrospectively the pooled results after pelvic exenteration for locally advanced T4 rectal cancer. Historically, patients with T4 rectal cancers requiring pelvic exenteration have been offered only palliative surgery or no operation. Methods: The basic treatment principle was preoperative (chemo)radiotherapy, radical surgery and, in some patients, adjuvant chemotherapy. Risk factors for local recurrence, distant metastases and overall survival were studied in univariable and multivariable analyses. Results: Ninety-five patients with T4 rectal cancer who underwent pelvic exenteration in two tertiary referral centres up to 2013 were studied. Clear margins (R0) were achieved in 87 per cent of patients. Adjuvant chemotherapy was administered in 33 per cent, independent of the resection margin, lymph node status and postoperative T category. The 5-year local recurrence rate was 17 per cent, with a distant metastasis rate of 16 per cent and overall survival rate of 62 per cent. In multivariable analysis the only factor associated with death was omission of adjuvant chemotherapy ( P = 0·016). The effect of adjuvant chemotherapy was more pronounced in the elderly: patients aged over 70 years who had chemotherapy had a 5-year overall survival rate of 80 per cent, compared with 39 per cent of elderly patients who did not receive chemotherapy ( P = 0·019). Conclusion: Pelvic exenteration led to an R0 resection rate of 87 per cent for T4 rectal cancer, giving good local control and overall survival comparable to population-based colorectal cancer survival rates. Adjuvant chemotherapy may improve overall survival further, even in the elderly. Abstract : Total pelvic exenteration gives local control and acceptable overall survival